Phytophthora agathidicida: research progress, cultural perspectives and knowledge gaps in the control and management of kauri dieback in New Zealand. (6th November 2019) - Bradshaw, R. E.; Bellgard, S. E.; Black, A.; Burns, B. R.; Gerth, M. L.; McDougal, R. L.; Scott, P. M.; Waipara, N. W.; Weir, B. S.; Williams, N. M.; Winkworth, R. C.; Ashcroft, T.; et al.
Abstract : Kauri ( Agathis australis ), which is one of the world's largest and longest‐living conifer species, is under threat from a root and collar dieback disease caused by the oomycete pathogen Phytophthora agathidicida . The noted incidence of kauri dieback has increased in the past decade, and even trees >1000 years old are not immune. This disease has profound effects on both forest ecosystems and human society, particularly indigenous Māori, for whom kauri is a taonga or treasure of immense significance. This review brings together existing scientific knowledge about the pathogen and the devastating disease it causes, as well as highlighting important knowledge gaps and potential approaches for disease management. The life cycle of P. agathidicida is similar to those of other soilborne Phytophthora pathogens, with roles for vegetative hyphae, zoospores and oospores in the disease. However, there is comparatively little known about many aspects of the biology of P. agathidicida, such as its host range and disease latency, or about the impact on the disease of abiotic and biotic factors such as soil health and co‐occurring Phytophthora species. This review discusses current and emerging tools and strategies for surveillance, diagnostics and management, including a consideration of genomic resources, and the role these play in understanding the pathogen and how it causes this deadly disease. Key aspects of indigenous Māori knowledge, which include rich ecological and historical knowledge of kauri forests and a holistic approach to forest health, are highlighted.